School management by values according to teachers' opinions - Arabaci, I. Bakir (Elsevier Science Bv, 2013)
Today,management by values has increased in value instead of management by regulations and norms. Internalized values of administrators and teachers at schools influence the improvement of organizational behaviours effectively. This research aims to determine the perceptions of teachers at primary schools about 'management by values' and if there is differentiation in successs according this perception or not. In research, survey methods are used. Research's sample is formed by 261 teachers working at schools in Elazig. Schools' successes were determined according to results in SBS. In result,participants adapt management by values in high levels. (C) 2013 The Authors. Published by Elsevier ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: Primary schools; Values; Management by values; Teachers' opinions